2019
DOI: 10.2147/ccide.s234851
|View full text |Cite
|
Sign up to set email alerts
|

<p>A New Method for Prediction of Dental Arch Perimeter</p>

Abstract: Purpose: Dental arch length, width, and perimeter are considered to be important for the diagnosis and treatment of orthodontic cases. This study aimed to utilize dental arch width and length to create an equation for predicting dental arch perimeter. Materials and methods: Sixty-seven pairs of study models for patients with normal occlusion who received dental treatment were included in this study. Dental arch width at the level of the canines, first premolars, and first molars, in addition to dental arch len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
0
5
1
Order By: Relevance
“…There were many studies showed the correlation between measurements of arch width using dental cast , [35][36][37] the highest correlation was between AL and ICW in both arches concluding that changes in one magnitude could change the other. [14][15][16]38] Our results couldn't be compared with those of Germane et al [35] where those authors found a correlation in patients with post-orthodontic treatment while our patients were have normal occlusion and don't experienced with orthodontic treatment before.…”
Section: Correlation Between Icw and Al Depicted Greater In Males As ...contrasting
confidence: 57%
See 2 more Smart Citations
“…There were many studies showed the correlation between measurements of arch width using dental cast , [35][36][37] the highest correlation was between AL and ICW in both arches concluding that changes in one magnitude could change the other. [14][15][16]38] Our results couldn't be compared with those of Germane et al [35] where those authors found a correlation in patients with post-orthodontic treatment while our patients were have normal occlusion and don't experienced with orthodontic treatment before.…”
Section: Correlation Between Icw and Al Depicted Greater In Males As ...contrasting
confidence: 57%
“…Motoyashi et al [36] also found that, the increase in arch perimeter as a result of intermolar mandibular growth, on the order of 0.37 mm, which was higher than the 0.27 described by Germane et al [35] AL-Ansari et al [16] found strong correlation between inter-canine width, inter-molar width, and arch length in the mandibular arch. [37] found that dental arch width and length had a direct, strong relationship with the dental arch perimeter.…”
Section: Correlation Between Icw and Al Depicted Greater In Males As ...mentioning
confidence: 83%
See 1 more Smart Citation
“…Landmarks were identified and drawn on the conventional stone cast with ultra-fine permanent pen marker. 23,24 The distances between the landmarks represented the measurements that were assessed in the study as follows:…”
Section: Methodsmentioning
confidence: 99%
“…It is claimed that arch length and width are correlated to arch perimeter in both the mandibular and maxillary arches, which subsequently affect the risk of crowding among children and adolescents (Al-Khatieeb et al 2012;Al-ansari et al 2019).…”
Section: Introductionmentioning
confidence: 99%